Measuring Variables That Affecting Listener’s Willingness to Subscribe Paid Music Streaming Application by Young-Adult in Jakarta and Bandung - Antonio, Kevin (Journal of Business and Management, 2017)
Absttrac. Listen to music is a habit that for some people it already becoming their primary needs, but since declining damage physical form music and the increasing of music piracy make a anxiety for listeners and for music industries. And paid streaming music application, become the solution of that phenomenas. To help this research the author use secondary data from website and paper study for the theoretical foundation. And in variables affecting listener willingness to subscribe paid streaming music application section that a part with 5 variables the author make one hypotheses in each variables, so there are 5 hypotheses in this research. This study will focus on undergraduate student in Jakarta and Bandung as the object of the study and the toatal population is 883.334 with using slovin sampling technique this reseach need 100 sample that will ask using quantitative questionnaire and will be analyze using conjoint analysis. After gather data and process it with conjoint analysis the author analyze each table of the result especially utility and average importance table in first combination package and second combination package. And after analyze each category the author compare the user and know group of respondents in each variable and end with overall discussion. And the findings are for the user the most important is application quality and for know the most important is price. Finally, the result of this research for the customer the ideal streaming music application is minimum in price variable and maximum in another variable, but the streaming music application company still can make trade off with all the combination and not must to set it like the customer ideal combination.Keywords: Music Piracy, Paid Streaming Music Application, Conjoint Analysis, and Willingness to Pay